The moonshiner's daughter - Everhart, Donna (Kensington Publishing Corp., 2020)
A young woman in 1960's North Carolina resents the moonshining operation her family has conducted for generations, blaming it for her mother's death. When her father insists that moonshining is in her veins, Jessie devises a plan to destroy the stills. Her scheme escalates an old rivalry and revels long-held grudges.